Entropy dynamics interpretation in genetic studies with the multifactor dimensionality reduction method - Ivaniukovich, Uladzimir A.; Melnov, Sergei B.; Min, Ma (Experimental Biology and Biotechnology, 2025)
The multifactor dimensionality reduction (MDR) method allows to select the predictor (gene, allele) combinations corresponding to a particular phenotype (outcome) with high precision. However, the entropy change graph and interaction dendrogram constructed in the MDR (version 3.0.2) software implementing this method do not characterize gene – gene interactions. Using examples of athlete classification based on their genotypes, it is shown that the software constructs a statistical entropy change graph when reducing dimensionality, which does not correspond to the strength and direction of real gene – gene interactions, but describes the efficiency of predictor convolution when combining two or more factors in order to achieve maximum accuracy in classifying outcomes.
Keywords: genetics; simulation; multifactor dimensionality reduction; gene – gene interactions; genotype; phenotype; entropy; statistical analysis; classification